2021
DOI: 10.3390/genes12081206
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on the Therapeutic Potentiality of PD-L1-Inhibiting MicroRNAs for Triple-Negative Breast Cancer: Toward Single-Cell Sequencing-Guided Biomimetic Delivery

Abstract: The programmed death-ligand 1 (PD-L1)/programmed cell death protein 1 (PD-1) is a well-established inhibitory immune checkpoint axis in triple-negative breast cancer (TNBC). Growing evidence indicates that tumoral PD-L1 can lead to TNBC development. Although conventional immune checkpoint inhibitors have improved TNBC patients’ prognosis, their effect is mainly focused on improving anti-tumoral immune responses without substantially regulating oncogenic signaling pathways in tumoral cells. Moreover, the conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 89 publications
1
27
0
Order By: Relevance
“…In this regard, single-cell sequencing of tumor bulk can help identify (potential) patient-specific neoantigens. Single-cell sequencing technologies can provide valuable insights into the expression profile of tumoral cells and categorize tumoral cells based on their neoantigens ( 15 , 51 ). Therefore, this categorization can allow us to develop personalized CAR-T cells with different molecular targets for each patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, single-cell sequencing of tumor bulk can help identify (potential) patient-specific neoantigens. Single-cell sequencing technologies can provide valuable insights into the expression profile of tumoral cells and categorize tumoral cells based on their neoantigens ( 15 , 51 ). Therefore, this categorization can allow us to develop personalized CAR-T cells with different molecular targets for each patient.…”
Section: Discussionmentioning
confidence: 99%
“…For our included in vivo studies, we utilized the “SYRCLE’s RoB” tool, adapted from the Cochrane RoB tool ( 13 ). For our included in vitro studies, we adapted the previously used quality assessment tool ( 14 , 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…ncRNAs regulating the PD-1/PD-L1 axis are able to change the sensitivity of cells toward pembrolizumab. For instance, miRNA-34a, 138, 200c, 424, and 570, let-7a, and lncRNAs CCAT1 and GATA3-AS1 can regulate tumor growth and proliferation through PD-L1 modulation, and thus response to immunotherapy [98][99][100]. In a clinical trial (KEYNOTE-086), Loi et al, using RNA-seq-based data, confirmed that inflammatory state signatures obtained by measuring the tissue-resident memory are asso-ciated with the response to pembrolizumab in TNBC patients [101].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TIGIT blockade can improve the efficacy of anti-PD-1 therapy and promote the stimulation of tumor-infiltrating CD8 + T-cells in patients with bladder cancer [ 42 ]. Besides, TIGIT/PD-1 dual blockade has remarkably improved anti-tumoral immune responses and promoted tumor rejection in lymphoma animal models [ 10 ]. Furthermore, the dual blockade of the immune checkpoint axes of PD-1 and TIGIT has been superior in rejecting melanoma and non-small-cell lung carcinoma [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…This axis can be established between immune and tumor cells and can substantially contribute to immunosuppressive tumor microenvironment development [8]. Although monoclonal antibodies targeting this inhibitory axis have been promising for some solid cancers, like triple-negative breast cancer, they have not yielded meaningful results in other solid cancers, like glioblastoma [9,10]. The low response rate of some patients to anti-PD-1 might be stemmed from the fact that other inhibitory immune checkpoint molecules can also regulate anti-tumoral immune responses.…”
Section: Introductionmentioning
confidence: 99%